Suitability of paludiculture biomass as biogas substrate − biogas yield and long-term effects on anaerobic digestion. (October 2020) - Hartung, Christina; Andrade, Diana; Dandikas, Vasilis; Eickenscheidt, Tim; Drösler, Matthias; Zollfrank, Cordt; Heuwinkel, Hauke
Abstract: Fen plants cultivated on wet peatlands might be an environmentally friendly alternative biogas substrate to maize and grass grown on drained peatlands. This study demonstrates that if Typha latifolia, Phragmites australis, and Phalaris arundinacea were harvested in mid-June, then their specific biogas yields (SBY) reached values of up to 581 L N kg −1 volatile solids (VS), which is similar to the SBY of grass, but lower than the SBY, of 670 L N kg −1 VS, for maize. Mixtures with equal or more than 10% T. latifolia or 40% P. arundinacea (VS-base) exhibited a reduced SBY compared to 100% maize silage in a batch-test. From the composition of the substrates, it remains unclear why fen plants degraded that poorly. However, during the semi-continuous long-term experiment, this effect led to an accumulation of non-degraded material, which destabilized the degradation process at loading rates above 3 kg VS m −3  d −1 . Destabilization became apparent with substantial increases in the viscosity of the fermenter content, enrichment of acids and a worsened methane formation. Our findings suggest that only small proportions of maize could be replaced by fen plants as substrate for biogas plants. Highlights: The specific biogas yield potential was highest for juvenile fen plants. The specific biogas yield decreased with increasing plant maturity. Higher proportions of fen plants reduced the specific biogas yield of maize silage. Poor degradability of fen plants caused technical and biological process problems.